Peran Penting Statistika dalam Pendidikan dan Perekonomian Islam Modern - Maswar Maswar; Diyah Ayu Rizki Pradita; Moh. Atikurrahman; Muslimin .; Saiful . (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
This research is a literature study with a descriptive qualitative approach to the type of literature that seeks to explain the important role of statistics in modern Islamic education and economics. In this literature study, researchers used various written sources such as books, articles, journals and other supporting documents relevant to the study. This study focuses on the discourse of statistical science and its role in the field of Islamic education and economics in the modern era. The results of the study show that statistics have been widely used by the public on various field such as politics, education, government, economics, and business. In education, statistics help students and learners or education practitioners in understanding data, measurement instruments, data analysis techniques, and drawing conclusions, both as evaluations and continuing education research. While in business, statistics can be applied to business calculations in the form of trend index numbers, dividend calculations, probability of profit in investments and stocks. Specifically, statistics have an important role in the banking sector, stock sector, capital market sector, insurance sector, multifinance and micro sector. Statistics present a lot of detailed and systematic information or data. Not only that, statistical science is highly recommended in Islamic economic and educational activities, and Allah likes people who carry out economic andeducational activities carried out with itqan, namely focused, clear, accurate, and compleKeywords: statistics, education, and modern islamic economy